Acetic acid-resistant topcon solar cell main grid silver paste glass powder and preparation method thereof
By preparing the acetic acid-resistant TopCon main gate silver paste glass powder composed of Pb3O4, SiO2, Bi2O3, etc., the corrosion problem of acetic acid steam on the glass layer is solved, and the welding tension and reliability of the TopCon components are improved.
Patent Information
- Application Number
- CN202411512562.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-10
AI Technical Summary
During the TopCon component packaging process, acetic acid steam will corrode the glass layer under the main gate, resulting in a reduction in welding tension and even causing electrode points to fall off. The existing technology is difficult to effectively solve this problem.
The glass powder with high acetic acid resistance TopCon main gate silver paste powder composed of Pb3O4, SiO2, Bi2O3, CuO, MnO2, etc. is prepared by mixing, smelting, quenching, ball milling and drying to form a glass powder with high acetic acid resistance.
During the packaging process of TopCon components, it can resist the erosion of acetic acid steam, maintain high welding tension, and significantly improve the reliability and service life of the components.
Smart Images

Figure CN119285239A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, in particular to an acetic acid resistant topcon solar cell main grid silver paste glass powder and a preparation method thereof. Background Art
[0002] As the current P-type solar cells in the photovoltaic industry are being rapidly replaced by N-type solar cells, among which N-type topcon cells are developing particularly rapidly. The main grid and the auxiliary grid are required on both the front and back of the topcon cells. During the metallization process, the glass powder in the main grid slightly corrodes the passivation layer without corroding through it, and mainly plays the role of connecting the silicon wafer and the silver layer, providing a certain welding tension. However, in the TopCon component packaging process, a certain amount of acetic acid vapor will be generated, corroding the glass layer under the main grid, resulting in a decrease in welding tension, and in severe cases, causing the electrode point to fall off. Therefore, the development of acetic acid-resistant TopCon main grid silver paste glass powder is an inevitable trend in the development of the industry. Summary of the invention
[0003] To achieve the above objectives, the present invention is implemented by the following technical scheme: an acetic acid resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 40-60 parts by mass of Pb3O4, 10-25 parts by mass of SiO2, 5-20 parts by mass of Bi2O3, 5-15 parts by mass of CuO, 3-15 parts by mass of MnO2, 0-8 parts by mass of B2O3, 0-8 parts by mass of TiO2, 0-5 parts by mass of Sb2O3, 0-5 parts by mass of ZrO2, 1-5 parts by mass of Al2O3, 0-5 parts by mass of P2O5 and 0-3 parts by mass of TeO2.
[0004] Preferably, it is composed of the following components: 45 parts by mass of Pb3O4, 18 parts by mass of SiO2, 11.5 parts by mass of Bi2O3, 12 parts by mass of CuO, 3 parts by mass of MnO2, 2 parts by mass of B2O3, 1 part by mass of TiO2, 2 parts by mass of ZrO2, 2 parts by mass of Al2O3, 2 parts by mass of P2O5 and 1.5 parts by mass of TeO2.
[0005] Preferably, the glass powder D10 is 0.1-0.5 μm; Preferably, the glass powder D50 is 0.9-1.2 μm; Preferably, the glass powder D90 is 2.5-5 μm; Preferably, the glass transition temperature is 300-550°C, the glass softening temperature is 350-650°C, and the glass melting temperature is 550-800°C.
[0006] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials Pb3O4, SiO2, Bi2O3, CuO, MnO2, B2O3, TiO2, Sb2O3, ZrO2, Al2O3, P2O5 and TeO2 according to weight percentage and mix them; Step 2: Put the raw materials weighed in step 1 into an alumina crucible, melt them in a box-type resistance furnace at 1100° C.-1350° C., and keep them warm for 20-40 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in step 2 in deionized water to obtain glass slag; Step 4: ball mill the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 1-15 mm, for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0007] The present invention provides an acetic acid resistant topcon solar cell main grid silver paste glass powder and a preparation method thereof. It has the following beneficial effects: This enables the topcon components to withstand the corrosion of acetic acid vapor and ensure a high welding tension during packaging, greatly improving the reliability and service life of the components. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is a schematic diagram of glass composition in an embodiment of the present invention; Figure 2 Schematic diagram of peel strength of an embodiment of the present invention. DETAILED DESCRIPTION
[0009] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
[0010] In the first embodiment, the present invention provides a technical solution: an acetic acid resistant topcon solar cell main grid silver paste glass powder, comprising the following components: 45% Pb3O4, 18% SiO2, 10.5% Bi2O3, 12% CuO, 3% MnO2, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0011] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 10.5% Bi2O3, 12% CuO, 3% MnO2, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0012] In the second embodiment, the present invention provides a technical solution: an acetic acid resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 9.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0013] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 9.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0014] In the third embodiment, the present invention provides a technical solution: an acetic acid-resistant topcon solar cell main grid silver paste glass powder, comprising the following components: 45% Pb3O4, 18% SiO2, 11.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0015] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 11.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0016] In the fourth embodiment, the present invention provides a technical solution: an acetic acid-resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 10.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0017] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 10.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0018] In the fifth embodiment, the present invention provides a technical solution: an acetic acid resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 10.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3 and 1.5% TeO2.
[0019] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 10.5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, ball milling time of 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0020] In the sixth embodiment, the present invention provides a technical solution: an acetic acid resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 10% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% P2O5 and 2% Al2O3.
[0021] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 10% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% P2O5 and 2% Al2O3 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, ball milling time of 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0022] In the seventh embodiment, the present invention provides a technical solution: an acetic acid resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 8,5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0023] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 8,5% Bi2O3, 12% CuO, 3% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0024] In the eighth embodiment, the present invention provides a technical solution: an acetic acid resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 8,5% Bi2O3, 6% CuO, 9% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0025] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 8,5% Bi2O3, 6% CuO, 9% MnO2, 2% B2O3, 1% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0026] In the ninth embodiment, the present invention provides a technical solution: an acetic acid-resistant topcon solar cell main grid silver paste glass powder, composed of the following components: 45% Pb3O4, 18% SiO2, 8,5% Bi2O3, 9% CuO, 3% MnO2, 2% B2O3, 4% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2.
[0027] A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder comprises the following steps: Step 1, weigh the raw materials 45% Pb3O4, 18% SiO2, 8,5% Bi2O3, 9% CuO, 3% MnO2, 2% B2O3, 4% TiO2, 3% Sb2O3, 2% ZrO2, 2% Al2O3, 2% P2O5 and 1.5% TeO2 by weight percentage and mix them; Step 2: Put the weighed raw materials into an alumina crucible, melt them in a box-type resistance furnace at 1100° C., and keep them warm for 20 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in deionized water according to step 2 to obtain glass slag; Step 4: ball milling the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 7.5 mm, and ball milling for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
[0028] As can be seen from Examples 1-6, selective experiments were conducted on B2O3, TiO2, Sb2O3, ZrO2, P2O5 and TeO2 based on Pb3O4, SiO2, Bi2O3, CuO, MnO2 and Al2O3 respectively. The results show that the peel strength of each example is different, and the difference between Example 3 and Example 5 is the most obvious. Example 3 shows the best acetic acid resistance without adding Sb2O3. It may be that during the sintering process, the glass powder softens and corrodes the passivation layer, thereby connecting the silicon wafer and the main grid. During the acetic acid fumigation process, the Sb element in the glass structure is not resistant to acid corrosion, resulting in a decrease in peel strength. The lack of P2O5 in Example 5 directly leads to lower peel strength before and after acetic acid. It is possible that the P element, as a network former, strengthens the network structure of the glass and improves the chemical corrosion resistance of the glass.
[0029] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. An acetic acid resistant topcon solar cell main grid silver paste glass powder, characterized in that: It is composed of the following components: 40-60 parts by mass of Pb3O4, 10-25 parts by mass of SiO2, 5-20 parts by mass of Bi2O3, 5-15 parts by mass of CuO, 3-15 parts by mass of MnO2, 0-8 parts by mass of B2O3, 0-8 parts by mass of TiO2, 0-5 parts by mass of Sb2O3, 0-5 parts by mass of ZrO2, 1-5 parts by mass of Al2O3, 0-5 parts by mass of P2O5 and 0-3 parts by mass of TeO2.
2. The acetic acid resistant topcon solar cell main grid silver paste glass powder according to claim 1, characterized in that: It is composed of the following components: 45 parts by mass of Pb3O4, 18 parts by mass of SiO2, 11.5 parts by mass of Bi2O3, 12 parts by mass of CuO, 3 parts by mass of MnO2, 2 parts by mass of B2O3, 1 part by mass of TiO2, 2 parts by mass of ZrO2, 2 parts by mass of Al2O3, 2 parts by mass of P2O5 and 1.5 parts by mass of TeO2.
3. A method for preparing acetic acid resistant topcon solar cell main grid silver paste glass powder, characterized in that: The following steps are involved: Step 1, weigh the raw materials Pb3O4, SiO2, Bi2O3, CuO, MnO2, B2O3, TiO2, Sb2O3, ZrO2, Al2O3, P2O5 and TeO2 according to weight percentage and mix them; Step 2: Put the raw materials weighed in step 1 into an alumina crucible, melt them in a box-type resistance furnace at 1100° C.-1350° C., and keep them warm for 20-40 minutes to obtain clarified glass liquid; Step 3, quenching the glass liquid in step 2 in deionized water to obtain glass slag; Step 4: ball mill the glass slag in step 3 in a ball mill, using zirconium oxide beads with a diameter of 1-15 mm, for 8 hours, and drying the obtained glass material at 80° C.; Step 5: Sieve the glass material in step 4 to obtain glass powder.
Citation Information
Cited By
Preparation method of silver-coated glass powder for solar cell silver paste
CN120943532A
Preparation method of silver-coated glass powder for solar cell silver paste
CN120943532B